Bardet-Biedl syndrome in a 19-year-old male: the first case report from Palestine - Karmi, Hamza B.; Abu Jwaid, Yahya; Shehadeh, Mohammad Hakam; Njoom, Dareen; Awwad, Aya; Eideh, Hasan (Frontiers in Pediatrics, 2024)
Bardet-Biedl syndrome (BBS) is a rare genetic disorder characterized by retinitis pigmentosa, polydactyly, type 2 diabetes mellitus, and obesity. This case report presents a 19-year-old male from Palestine with BBS, exhibiting delayed diagnosis and variable phenotypic expression. The patient had familial BBS history and presented with obesity, type 2 diabetes mellitus, retinitis pigmentosa, and cryptorchidism. Genetic analysis identified heterozygous missense variants in the FBN3 gene, yet additional genetic factors may contribute to the phenotype. Renal abnormalities included kidney shrinkage and mild hydronephrosis. Management of this patient involves a multidisciplinary approach with lifestyle modifications, surgical interventions, and supportive care. Early diagnosis, genetic counseling, and regular follow-up are crucial for improving outcomes in BBS. This report highlights diagnostic and therapeutic challenges and underscores the need for further research on this complex disorder.